The Tragedy of Stillbirths Globally. Issue 1 (January 2018) - Callister, Lynn Clark
Abstract : In 2015, there were 2.6 million stillbirths globally, with 1.3 million occurring during labor and birth. Twenty countries have the highest rates of stillbirths, accounting for 76% of those deaths. Ninety-eight percent of stillbirths occur in low and middle income countries. Current efforts to prevent stillbirths are discussed by Dr. Callister, our expert on global health and nursing